2006
DOI: 10.1080/10407790500291921
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Lifted Methane Jet Fires Using the Boundary-Layer Equations

Abstract: The focus of this paper is turbulent lifted jet fires. The main objective is to present a lifted jet fire methodology using the boundary layer equations as a basis. The advantages of this are finite volume mesh independent predictions of the mean flow fields can be calculated on readily available computer resources which leads to rigorous model calibration. A number of lift-off models are evaluated. The model of choice is one based on the laminar flamelet quenching concept combined with a model for the large-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
0
14
2
Order By: Relevance
“…Sanders and Lamers based on an isothermal jet calibration concluded the small-scale strain rate model to be the superior of the two with respect to predicting the lift-off heights in methane jet fires; however in a recent paper Cumber and Spearpoint, [32] demonstrated that the largescale strain rate model gave a better calibration against Wittmer's lift-off measurements, [33] the data used by Sanders and Lamers. Further studies not reported here, comparing Kalghatgi's liftoff height measurements [6] with the predicted lift-off height using the two strain rate models, for a range of methane and propane jet fires further confirmed the superiority of the large-scale strain rate model.…”
Section: Turbulent Combustion Modelmentioning
confidence: 99%
“…Sanders and Lamers based on an isothermal jet calibration concluded the small-scale strain rate model to be the superior of the two with respect to predicting the lift-off heights in methane jet fires; however in a recent paper Cumber and Spearpoint, [32] demonstrated that the largescale strain rate model gave a better calibration against Wittmer's lift-off measurements, [33] the data used by Sanders and Lamers. Further studies not reported here, comparing Kalghatgi's liftoff height measurements [6] with the predicted lift-off height using the two strain rate models, for a range of methane and propane jet fires further confirmed the superiority of the large-scale strain rate model.…”
Section: Turbulent Combustion Modelmentioning
confidence: 99%
“…The issue of robust calibration is a particularly important one as without it, model development looses rigour. Cumber and Spearpoint (2006) showed that Sanders and Lamers (1994) adoption of the small-scale strain rate model for lifted methane jet fires was incorrect as the large scale strain rate model gave far closer agreement with observed lift-off heights once both models were calibrated appropriately. In the next section the mathematical model is presented.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of small-scale, Kalghati (1984) and Pitts (1989) and large-scale experimental studies of lifted fires, Birch and Hargreave (1988) exist in the open literature. There are also a number of theoretical studies, Sanders and Lamers (1994), Cumber and Spearpoint (2006) being examples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations